Tropicron Polyester Fiber Corporation Marikina, Rizal plant design for the manufacture of polyester fiber - Quitoriano, Mario I.; Ramos, Liberato F.; Caducio, Vicente (Diliman, Quezon City College of Engineering, 1969)
The design report discusses the manufacture of polyester fiber using ethylene glycol and dimethyl terephthalate as raw materials. Aside from the primary product, methanol of marketable grade is derived as a by-product. The whole manufacturing scheme is divided into three main steps : re-esterification, polymerization and spinning. Included in the report is the economic feasibility of the industry. From previous market survey, the plant capacity was determined to be 1500 MT per year. With this capacity, the required initial investment is P5,958,824. The sales derived from the product and by product combined is P15,191,192, while the total cost of manufacture is P10,098,608, giving a profit of P5,092,584 before taxes or P3,310,180 after taxes. The pay-out time is 1.045 years before taxes or 1.556 years after taxes. These figures make evident the necessity for the immediate construction of the plant. It is recommended that the plant be put up in Marikina, Rizal.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Polyester fibers industry; Polyester fibers